Combination of Gallery Well Reactor And Slow Sand Filtration For Clean Water Reclamation in Flooded Area (Study Case: Morowudi Village, Gresik District) - febrianti, aulia nur febrianti; Pungut, Pungut; Tribhuwaneswari, Annisa Budhiyani (Journal of Research and Technology, 2024)
In Morowudi Village, Gresik, flooding is a known problem frequently brought on by excessive rainfall and inadequate drainage infrastructure. The ensuing floods make it difficult for the nearby towns to have safe drinking water. Sand Slow filter technology is suggested as a solution to this problem. Establishing parameter levels, lowering parameters, and evaluating the efficiency of different filtration media in lowering turbidity, iron metal, and total coliforms in flooded raw water in the Morowudi, Gresik area are the goals of this study. Using a batch method, the research will be conducted in a laboratory setting after the floodwater has been using the gallery well procedure. The study will concentrate on three different types of filtration media: 70 cm of silica sand media will be used in the first reactor, iron sand filtration media will be used in the second reactor, and beach sand filtration media will be used in the third reactor. Sand media with sizes ranging from 0.25 to 0.5 mm will be used in all reactors, and layers of 5–10 mm and 10–20 mm gravel will be added as supplements in total of 20 cm. The result showed that the efficacy of turbidity reduction can exceed 57.62%. The efficacy of TDS reduction is established at 10.26%, whereas the efficacy of total coliform reduction is established to be over 83%.